The role of p53 in the alternation of vascular functions - Chan, Gabriel Hoi-Huen; Chan, Enoch; Kwok, Carsten Tsun-Ka; Leung, George Pak-Heng; Lee, Simon Ming-Yuen; Seto, Sai-Wang (Frontiers in Pharmacology, 2022)
Ageing is a risk factor for many degenerative diseases. Cardiovascular diseases (CVDs) are usually big burdens for elderly, caregivers and the health system. During the aging process, normal functions of vascular cells and tissue progressively lost and eventually develop vascular diseases. Endothelial dysfunction, reduced bioavailability of endothelium-derived nitric oxide are usual phenomena observed in patients with cardiovascular diseases. Myriad of studies have been done to investigate to delay the vascular dysfunction or improve the vascular function to prolong the aging process. Tumor suppressor gene p53, also a transcription factor, act as a gatekeeper to regulate a number of genes to maintain normal cell function including but not limited to cell proliferation, cell apoptosis. p53 also crosstalk with other key transcription factors like hypoxia-inducible factor 1 alpha that contribute to the progression of cardiovascular diseases. Therefore, in recent three decades, p53 has drawn scientists’ attention on its effects in vascular function. Though the role of tumor suppressor gene p53 is still not clear in vascular function, it is found to play regulatory roles and may involve in vascular remodeling, atherosclerosis or pulmonary hypertension. p53 may have a divergent role in endothelial and vascular muscle cells in those conditions. In this review, we describe the different effects of p53 in cardiovascular physiology. Further studies on the effects of endothelial cell-specific p53 deficiency on atherosclerotic plaque formation in common animal models are required before the therapeutic potential can be realized.